LOLR policies, banks' borrowing capacities and funding structures - Stefano Corradin; Suresh M. Sundaresan (European Central Bank (ECB), 2022)
We investigate banks' benefits and costs of having access to LOLR. Integrating novel data sets we estimate the borrowing capacities of euro area banks at the ECB. Controlling for ratings, we find that banks with more fragile funding are likely to borrow more from the ECB during the great financial and euro area sovereign debt crises. We develop a dynamic model of a bank and calibrate it to our empirical estimates. A bank with access to LOLR has higher equity value and makes larger investments in new loans, but it is more leveraged, pays more dividends and issues less equity.
Keywords: G2; E5; E58; 330; LOLR; Collateral; Haircut; Borrowing Capacity; Liquidity